Towards smart & sustainable farming of Kelulut at IIUM - Azhar, Nur Aida Elyna; Suhaimi, Abu Dzar; Amir, Adibah; Syed Shaharuddin, Sharifah Imihezri; Mohd. Zaki, Syazwani (2021)
Kelulut or stingless bees are a large group of bees that are closely related to honeybees but the major difference between the two species is that stingless bees cannot sting. On average, a typical kelulut colony size consists of 1000 to 10 000 bees. Due to the kelulut’s small size, they can only travel and forage up to 800 meters only compared to honeybees where they can go up to 2 kilometers. While stingless bee honey is different from the ones produced by honeybees in terms of color, viscosity, and taste, the nutritional value and health benefits of stingless bee honey do not come short of ordinary honey. Researchers believe that stingless bee honey is twice as nutritious as ordinary honey and are known for its antioxidant, anti-microbial, anti-inflammatory, anti-cancer and wound healing activity properties.